Accounting and tax accounting of derivative financial instruments - Султанова, Б. (Journal of Economic Research & Business Administration, 2017)
Financial markets debt and equity markets, suggest an immediate supply of a financial asset, so they are called cash markets or spot markets. Other markets operate contracts to buy or sell an asset at some point in the future. The owners of this contract shall have the right or obligation to buy or sell a financial asset at a specified price on a specified day. The price of this contract is a derivative of the price of the asset. Therefore such contracts are called derivatives. Derivative financial instruments are one of the most complex accounting objects. The paper deals with the recognition and measurement of derivative financial instruments in accordance with IFRS (IFRS) 9 “Financial Instruments” and IFRS (IAS) 39 “Financial Instruments: Recognition and Measurement”. This article discusses the general principles of tax accounting of derivative financial instruments adopted in Kazakhstan’s tax practice, as well as the basic provisions of § 5. Derivative financial instruments of the Tax Code of the Republic of Kazakhstan.